2007
DOI: 10.1111/j.1745-4530.2007.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mechanical Properties of Some Selected Almond Cultivars With Hard and Soft Shell Under Compression Loading

Abstract: The mechanical properties of Nonpareil versus Gulcan 101‐23 almond cultivars that have different shell properties were loaded between two parallel plates to determine the rupture force, rupture energy, rupture power requirement, toughness and firmness. The tests were carried out with three moisture contents, namely, 7.2, 22.9 and 33.6% wet basis and three loading axes (x, y, z). Physical characteristics of the almond cultivars such as length, width, thickness, geometric mean diameter, sphericity, volume, surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
5
19
0
Order By: Relevance
“…The decrease in rupture force may be a result from softening the walnut at higher moisture content. Similar conclusions were also made by Braga et al (1999) for macadamia nut; Güner et al (2003) for hazelnut; Khazaei et al (2002) and Aktas et al (2007) for almond; and Sharifian and Derafshi (2008) for walnut.…”
Section: Rupture Forcesupporting
confidence: 75%
See 2 more Smart Citations
“…The decrease in rupture force may be a result from softening the walnut at higher moisture content. Similar conclusions were also made by Braga et al (1999) for macadamia nut; Güner et al (2003) for hazelnut; Khazaei et al (2002) and Aktas et al (2007) for almond; and Sharifian and Derafshi (2008) for walnut.…”
Section: Rupture Forcesupporting
confidence: 75%
“…where P r is the rupture power required of walnut (W), E is the rupture energy (mJ), V is compression speed (mm/min), and D is the corresponding deformation at the rupture point (Olaniyan and Oje 2002;Khazaei et al 2002;Aktas et al 2007). …”
Section: Determination Of Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…400 N to achieve the shell's rupture. On the other hand, the European cultivars showed a resistance of the shell greater than 600 N, and in the case of 'Supernova' almost 1,000 N. The comparison of 'Nonpareil' with a hard-shelled Turkish cultivar showed rheological differences between them, and it was concluded that the industrial processing should be different per each cultivar [23].…”
Section: Characterization Of the Nutmentioning
confidence: 93%
“…So far many studies have been conducted on physical and mechanical properties of hard shelled nuts and kernels as hazelnut, pistachio nut, apricot, pine nut, almond, walnut, macadamia nut and cashew nut by Oloso & Clarke (1993), Liu et al (1999), Borghei et al (2000), Aydın (2002), Gezer & Dikilitaş (2002), Aydın (2003), Güner et al (2003), Vursavuş & Özgüven (2004), Vursavuş & Özgüven (2005), Aktaş et al (2007), Arslan & Vursavuş (2008) and Galedar (2009). There are also a few studies on physico-mechanical properties of chestnut.…”
Section: Introductionmentioning
confidence: 99%